PENGARUH MOTIVASI, LINGKUNGAN KELUARGA DAN LINGKUNGAN SEKOLAH TERHADAP MINAT BELAJAR PADA MATA PELAJARAN KOMPUTER AKUNTANSI SISWA KELAS X SMK MUHAMMADIYAH 1 PEKANBARU - Ningsih, Lulu Tia; Gimin, Gimin; Sumarno, Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of motivation, family environment and school environment on learning interest in accounting computer subjects in class X of Muhammadiyah 1 Vocational School Pekanbaru. The total population in this study was 65 students from 2 classes X accounting. The sample in this study was taken as much as the population so that this study is a population research. The type of data used in this study is primary data. Data collection techniques using questionnaires. Data analysis using descriptive analysis and multiple linear regression. The results showed that students' motivation was still in the low category, the family environment was still in the low category, the school environment was in the low or less optimal category, and the interest in learning was still in the low category. Motivation, family environment and school environment have a significant effect on interest in learning with the regression equation Y = 0.205a + 0,214X1 + 0,221X2 + 0,149X3 and contribute to students' learning interest of 38,8%.Key Words: Motivation, Family Environment, School Environment and Learning Interest